Balanced Growth using Ontology-based Tantra Framework - Mooror Prabhu, Shreekanth; Balasubramanya Murthy, K. N.; Natarajan, Subramanyam (Journal of Information and Knowledge, 2019)
Indian Economy is one of the fastest growing economies in the world, currently growing at around 7%. However, India’s growth has been highly uneven and lop-sided. Sectors such as services relying on exports have grown far more whereas manufacturing and agriculture have languished. As global trade environment becomes tougher, there is increasing realization that India’s domestic economy needs to grow lot more. In this context, balanced growth theory proposed by Ragnar Nurkse and many other Economists in 1950s is worth revisiting. Nurkse called for unleashing growth across different sectors of domestic economy simultaneously. Nurkse identified productivity as key determinant of market size and considered the poor as participants in the growth process than as mere beneficiaries. Even though balanced growth model is an ideal to aspire for, there are very few success stories which laid a clear roadmap to achieve it. Further, we need to reimagine the balanced growth model for today’s context to take into consideration newer challenges and opportunities compared to 1950s. In addition, the role of the Government needs to be recalibrated to be a catalyst in market economy in contrast to planned economies. To accomplish this complex task, we need an information framework that has an ecosystem approach and looks at society holistically. We propose the use of Ontology-based Tantra Social Information Management Framework to steer India towards the balanced growth ideal. This paper contains the description of Tantra Framework and our approach to realize balanced growth using Tantra Framework.